The Association Between Leisure-time Physical Activity, Sedentary Behavior, and Low Back Pain: A Cross-sectional Analysis in Primary Care Settings - Lemes, Ítalo Ribeiro [UNESP]; Pinto, Rafael Zambelli; Turi Lynch, Bruna Camilo; Codogno, Jamile Sanches [UNESP]; Oliveira, Crystian Bitencourt [UNESP]; Ross, Leanna M.; Araújo Fernandes, Rômulo [UNESP]; Monteiro, Henrique Luiz [UNESP] (Wolters Kluwer, 2021)
STUDY DESIGN: Observational cross-sectional. OBJECTIVE: To investigate the association between leisure-time physical activity (LTPA) and low back pain (LBP) in adults from primary care settings, and to explore how sedentary behavior influences this association. SUMMARY OF BACKGROUND DATA: LTPA is inversely associated with LBP. However, there is no study investigating this association in primary care settings from a middle-income country. Moreover, the influence of sedentary behavior in this association is unknown. METHODS: Cross-sectional analysis of an ongoing longitudinal study with adults from Bauru, Brazil (n = 557). Data on physical activity, sedentary behavior (sitting time), LBP, body mass index (BMI), and chronic diseases were assessed by face-to-face interviews, physical evaluation, and medical records. Binary logistic regression was used to test the association of LTPA with the presence of LBP. Sociodemographic, behavioral, and health variables were used as covariables in the multivariable models. RESULTS: The fully adjusted model showed that active participants were 33% less likely to have LBP when compared with those insufficiently active (odds ratios [OR]: 0.67 [95% CI: 0.46-0.98]). A significant association was found for active participants who spent less than 3 h/day sitting (OR: 0.45 [95% CI: 0.23-0.89]) but not for those who spent 3 h/day or more in sedentary activities (OR: 0.78 [95% CI: 0.48-1.27]). An inverse association of LTPA with LBP was observed in obese participants (OR = 0.49 [95% CI: 0.25-0.94]), but not in those with normal BMI and overweight. CONCLUSION: LTPA was inversely associated with the prevalence of LBP in adults from primary care. This association was influenced by sedentary behavior and BMI.Level of Evidence: 4.